Pendidikan Pencegahan dan Penanganan Stunting Menggunakan Model Ma-Kataroa Ndai pada Masyarakat - Nurwahidah, Nurwahidah; Syaiful; Imam Fadhlullah Pratama; Annisa Dwi Kemalahayati; M.Fahrurrahman (Jurnal Pengabdian Masyarakat Cendikia Jenius, 2025)
This community service activity aimed to improve public knowledge and awareness regarding the prevention and management of stunting through the implementation of the Ma-Kataroa Ndai model in Jatibaru Village, Asakota District, Bima City. The method consisted of preparation, implementation, monitoring, and evaluation stages. Activities were carried out through health education, community outreach, and collaborative efforts involving local health cadres and community leaders. Educational materials included leaflets, banners, and teaching booklets, supported by the provision of nutritious food as a practical example. The results showed a significant increase in community knowledge, with respondents in the “good” category rising from 15% in the pre-test to 80% in the post-test, while those in the “poor” category decreased from 37.5% to 0%. This program also encouraged active community participation in maintaining environmental sanitation and fulfilling children’s nutritional needs through self-help initiatives such as weekly rice collection and egg provision. In conclusion, the Ma-Kataroa Ndai model proved effective in enhancing community understanding and awareness of stunting prevention while promoting collective engagement for the sustainability of health programs at the community level.